Cognitive and Behavioral Inhibition Deficits in Parkinson’s Disease: The Hayling Test as a Reliable Marker - Siquier, Antònia; Andrés, Pilar (Frontiers in Aging Neuroscience, 2021)
Objective. The present study seeks to provide an overview of executive (inhibition and flexibility) deficits in Parkinson’s disease (PD) by combining a cognitive and behavioral approach. Methods. 15 PD patients and 15 healthy controls underwent a neuropsychological and behavioral assessment including the Hayling and Trails Tests, the Questionnaire for Impulsive–Compulsive Disorders in Parkinson’s Disease (QUIP-RS), the Behavior Rating Inventory of Executive Function (BRIEF-A) and the Short Form-36 Health Survey (SF-36). The level of awareness of executive functioning was also analyzed. We finally explored how these neuropsychological and clinical outcomes could relate to each other. Results. PD patients performed significantly worse in both neuropsychological tasks designed to evaluate inhibition abilities. They also reported more inhibition difficulties in everyday life and poorer quality of life. Associations between neuropsychological measures and self-reports were found. Moreover, as indicated by the discrepancy score, PD patients were as accurate as their relatives in self-reporting their executive daily difficulties. Conclusions. Inhibition and cognitive flexibility impairments assessed by the neuropsychological tests (Hayling and Trails tests) seem to capture daily life executive problems in PD. Furthermore, our study provides a deeper understanding of PD patients’ and their relatives’ experience of these executive dysfunctions.